Participatory evaluation of advanced potato (Solanum tuberosum) clones for water stress tolerance - Arya, S.; Rawal, S.; Luthra, S.K.; Sharma, N.; Gupta, V.K.; Kadian, M.S. (2017)
An attempt was made to introduce potato (Solanum tuberosum L.) in hot arid water scarce zone of Western Rajasthan, India. Eight CIP-bred potato clones were evaluated along with two controls, viz. Kufri Pukhraj and Kufri Surya on farmer’s field at Jodhpur, Rajasthan under normal and moderate water stress regime during three winter crop seasons (2012-15). Pooled analysis revealed that CIP clone 397006.18 (34.0 tonnes/ha) out yielded Kufri Pukhraj (26.8 tonnes/ha) and Kufri Surya (20.2 tonnes/ha) for marketable tuber yield. This clone maintained yield under normal and deficit irrigation and attained 26.9% higher marketable yield under normal irrigations, which further improved by 31.3% under deficit water stress regime over the best control Kufri Pukhraj. This clone recorded highest tuber dry matter content (22.7%), statistically superior to both control Kufri Pukhraj (17.9%) and Kufri Surya (21.4%). Clone 397006.18 had highest mean drought tolerance index value (1.16) and least total weight loss under normal irrigation (4.9%) and water stress conditions (8.6%) up to 60 days of storage. Preference yield analysis by potato growers showed that they liked this clone most and its overall acceptability was fairly better for all organoleptic traits. Results of field study and participatory varietal selection indicated that clone 397006.18 performed better for tuber productivity under deficit water management, exhibited drought tolerance traits and achieved overall acceptance by the farmers in Western Rajasthan.